2003
DOI: 10.1016/s0361-090x(03)00027-8
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of serum iron, ferritin, nitrite, and association with risk of renal cancer in women

Abstract: Reliability of serum levels of iron, ferritin and nitrite (NO 2 − ) over a 2-year period were evaluated in 40 healthy women (20 pre-menopausal and 20 post-menopausal), ages 39-65 years, from the New York University Women's Health Study (NYUWHS). Three blood samples per woman collected at yearly intervals were analyzed. Reliability coefficients (RCs) of serum iron, ferritin, and nitrite were 0.03 (95% confidence interval ( In a case-control study nested within NYUWHS cohort, serum levels of nitrite, ferritin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
(41 reference statements)
1
27
0
Order By: Relevance
“…This result is in agreement with previous studies (17,(24)(25)(26). The high reliability of circulating ferritin coupled with its positive correlation with residual iron stores, measured by using quantitative phlebotomy (27), makes it a valuable assay in epidemiologic studies.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This result is in agreement with previous studies (17,(24)(25)(26). The high reliability of circulating ferritin coupled with its positive correlation with residual iron stores, measured by using quantitative phlebotomy (27), makes it a valuable assay in epidemiologic studies.…”
Section: Discussionsupporting
confidence: 94%
“…Preparation of serum samples, as well as techniques for determining ferritin, SI, UIBC, TIBC, transferrin saturation rate (percent), and HMdU aAb titers, were described previously (15,17,18). sTfR in sera was determined by using an enzyme-linked immunosorbent assay technique using two different monoclonal antibodies specific for sTfR (R & D System, Minneapolis, MN).…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Transferrin saturation rates between the two types of mice were similar to those between pre-and postmenopausal women. (16,17) Serum E2 levels were comparable and remained low, simulating menopause. Figure 4B demonstrates that BMD was significantly lower in iron-accumulated HFE þ/À mice than in WT mice.…”
Section: Inhibitory Effects Of Iron On Alp Activity and Mineralizationmentioning
confidence: 97%
“…Using data collected initially from the New York University (NYU) Women's Health Study, we observed that ferritin, an iron storage protein with the capacity to bind up to 4,500 atoms of iron, and transferrin, an iron-transport protein with two binding sites for iron, are significantly higher in post-than in premenopausal women. (9) A subsequent literature search of large population studies demonstrated that concurrent but inverse changes occur in levels of ferritin and estrogen during the menopausal transition. (10) The normal functions of ovaries and menstruation lead to systemic levels of high estrogen but low iron in young women.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent study from Sweden, with a sample size of more than 200,000, reported no association between serum iron and cancer risks at most sites (1). In earlier studies, both negative (2)(3)(4)(5) and positive associations (6-8) have been described. Even among those studies reporting a positive correlation, the observed risk varied by cancer type and by gender (6)(7)(8).…”
Section: Introductionmentioning
confidence: 97%